Plan de negocios para una planta de procesamiento de café en la ciudad de Santa Elena - Pincay Vélez, Alexis Alejandro (2026)
The objective of the research is to evaluate the feasibility of establishing a coffee processing plant in the province of Santa Elena, based on an analysis of local demand, market potential, as well as the product’s value chain (supply, processing, distribution, and commercialization). To this end, a quantitative methodology was developed, supported by the use of official statistical information and a market study aimed at understanding consumers’ consumption habits, preferences, purchase frequency, and willingness to pay. In the fieldwork, 381 surveys were conducted using structured questionnaires, which made it possible to collect primary data and carry out descriptive statistical analysis (frequencies, percentages, and trends). To estimate per capita consumption and forecast future demand, the chained ratios method was used, complemented by projection techniques such as moving averages and annual percentage growth to identify market behavior and its expected evolution in the coming years. The results showed an estimated total demand of 487.5 tons for 2023, with a projected annual growth of 4%, confirming a favorable scenario for investment. In addition, an unmet demand of 75% was identified, representing a concrete opportunity for the entry of a processing plant capable of supplying the market in a timely manner and with competitive quality standards. It was also determined that coffee consumption in Santa Elena is influenced by factors such as tourism increasement, growth in the sector of service, and the opening of new consumption venues (coffee shops, restaurants, and related businesses), elements which energize the market and strengthen expansion prospects. Finally, the importance of adequate operational and financial planning, efficient resource management, and the establishment of sustainable partnerships with local producers is highlighted to ensure supply, final product quality, and competitiveness in the regional market.